NATIONAL VALUES AS A FACTOR IN THE DEVELOPMENT OF HUMAN CAPITAL IN THE NEW UZBEKISTAN - Markayev Zokir Eshkulovich; Kuyliyev Tulkin (Zeta Repository, 2023)
The article reveals that the importance of national and spiritual values in the life of a person and society is increasing, and their role in the development of youth is becoming increasingly important for all of us. In the accumulation of human capital, human potential and the corresponding capital are distinguished. Without education, human capital cannot be formed, used or profited from it. It follows that education is one of the main components of human capital and is closely related to such concepts as the education system, educational service, quality of education and social cooperation. Also in the article, human potential exists as a reserve and is analyzed as a kind of opportunity to become human capital, which manifests itself only in the process of economic activity.